Awareness on Tuberculosis treatment and the socio demographic factors influence on compliance of Tuberculosis treatment among the patients at the Chest clinic Jaffna - Alshan, M.S.M.; Kamalarupan, L.; Jamunanantha, C.S. (University of Jaffna, 2023)
Introduction: Tuberculosis (TB) is a major global public health problem and one of the leading causes of death among infectious diseases. Noncompliance with the treatment remains the main challenge for TB prevention and control. Poor compliance may cause prolonged disease infectiousness, drug resistance, relapse, and death. Multiple underlying factors linked to noncompliance with treatment need to be addressed to promote compliance with treatment. Objective: To assess awareness of Tuberculosis treatment and identify the influence of socio-demographic factors on compliance with TB treatment among TB patients in the chest clinic, Jaffna. Methodology: A descriptive cross-sectional study was conducted among patients who were ≥18 years registered from 1 st of June 2020 to 31st of May 2022 with pulmonary tuberculosis in the Chest clinic, Jaffna. Data was collected by using an interviewer-administered questionnaire and statistical software SPSS 25 is used to analyse the data. Data was presented in frequencies and percentages and Chi-square test was used to find the association. Ethical approval was obtained from ERC, Faculty of Medicine, University of Jaffna. Results: Totally 259 patients participated in the study. The mean age was 56.6 years. The majority of the study participants were males (70.3%). Most of them were Sri Lankan Tamils (84.2%). Among them, 78.4% patients had good treatment compliance. Almost all of them (99.2%) knew the duration of the Tuberculosis treatment period as 6-12 months and they were aware that Tuberculosis can be cured by regular treatment (87.6%). BCG is given to prevent primary Tuberculosis (91.1%), Most of them (94.6%) knew sputum samples are used to diagnose pulmonary Tuberculosis. Also, nearly 70% were aware of Tuberculosis treatment. Age, education level, occupation and family monthly income, were shown the statistical significance with the treatment compliance on Tuberculosis. Conclusion: The majority of the participants had good treatment compliance. Age, education level, occupation and family monthly income were showed the statistical significance with the Tuberculosis treatment.
Keywords: Tuberculosis; Treatment; Compliance; Factors